Pattern and Process in Cultural Evolution - Shennan, Stephen (Book collections on Project MUSE., 2009)
This volume offers an integrative approach to the application of evolutionary theory in studies of cultural transmission and social evolution and reveals the enormous range of ways in which Darwinian ideas can lead to productive empirical research, the touchstone of any worthwhile theoretical perspective. While many recent works on cultural evolution adopt a specific theoretical framework, such as dual inheritance theory or human behavioral ecology, Pattern and Process in Cultural Evolution emphasizes empirical analysis and includes authors who employ a range of backgrounds and methods.